Uji Sitotoksik Ekstrak dan Fraksi Dendrophtoe pentandra (L) Miq pada sel T47D - Masayu Farah Diba; Salni Salni; Subandrate Subandrate (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2019)
Indonesia has a variety of plants that have the potential for medicine. One of the plants used by the community as a drug with anticancer effects is Dendrophtoe petandra (L.) Miq. This study aims to determine the cytotoxic effect of ethanol extract, ethyl acetate fraction and water ethanol fraction of Dendrophtoe petandra (L.) Miq on T47D breast cancer cells. The cytotoxic effects of ethanol extract, ethyl acetate fraction and water ethanol fraction were carried out by MTT assay method using series concentration. Cytotoxic effects were assessed by calculating IC50 values using linear equations. Phytochemical test showed that Dendrophtoe petandra (L.) Miq contained saponins, terpenoids, flavonoids and tannins. The IC50 value of the ethanol extract, ethyl acetate fraction and water ethanol fraction were 417.506 μg/mL, 233.617 μg/mL, and 2748.357 μg/mL, respectively. The smaller the IC50 value means that the compound is more active. Water ethanol fraction of Dendrophtoe petandra (L.) Miq does not have a cytotoxic effect, whereas ethanol extract and ethyl acetate fraction of Dendrophtoe petandra (L.) Miq have cytotoxic effects in the medium strength category. The content of flavonoids and saponins in ethanol extract and ethyl acetate fraction of Dendrophtoe petandra (L.) Miq is thought to play role in causing T47D cell death. Cytotoxic effects of ethyl acetate fraction are stronger than ethanol extracts.